Study of machinability on drilling austenite stainless steel 316 L1 by solid cabide tool - Norsyeeda, Ab Alim (2012)
Austenite stainless steel is one of the most important engineering materials with wide variety of applications. Superior resistances to corrosion and compatibility in high temperature and high vacuum have particularly made it an attractive choice. However, the machinability of austenitic stainless steel is not very promising owing to lower thermal conductivity, higher degree of ductility and work harden ability. Grade 316 L1 is the standard molybdenum- bearing grade. Molybdenum gives 316 better corrosion resistance properties than crevice corrosion in chloride environment. It has excellent forming and welding characteristics. Over the years, cemented carbide (WC-Co) has overcome many drawbacks of high speed steel (HSS) as cutting tool materials and become one of the most versatile cutting tool materials during machining both ferrous and non ferrous alloys. There are mainly three grades of cemented carbide cutting tool example K, P and M grades. Steel being very ductile in nature produces long, continuous chip during machining. Moreover, iron in steel has greater affinity towards carbon of WC of the tool. P grade, is more diffusion resistant grade due to presence of more stable carbide like TiC, TaC and NbC. Therefore, P grade is also known as mixed carbide grade and more suitable for machining steel. Since P30 grade of cemented carbide would provide excellent balance of hardness, wear resistance and toughness, the same grade has been chosen for machining of stainless steel. In the first phase of work, tool life test would be carried out using three different cutting velocities (110, 130 and 150 m/min) with constant feed of 0.2mm/rev and constant depth of cut of 1mm for different duration of machining. Tool life study would be based on average flank wear, VB= 0.3 mm criterion. Flank wear would be measured using a zoom optical microscope. Therefore, effect of cutting speed on tool life of uncoated P30 grade carbide insert would be studied during machining of 316 grade of austenitic stainless steel.